Modeling, Simulation and Optimization of Bipedal Walking - Mombaur, Katja (Springer, 2013)
The model-based investigation of motions of anthropomorphic systems is an important interdisciplinary research topic involving specialists from many fields such as Robotics, Biomechanics, Physiology, Orthopedics, Psychology, Neurosciences, Sports, Computer Graphics and Applied Mathematics. This book presents a study of basic locomotion forms such as walking and running is of particular interest due to the high demand on dynamic coordination, actuator efficiency and balance control. Mathematical models and numerical simulation and optimization techniques are explained, in combination with experimental data, which can help to better understand the basic underlying mechanisms of these motions and to improve them. Example topics treated in this book areModeling techniques for anthropomorphic bipedal walking systemsOptimized walking motions for different objective functionsIdentification of objective functions from measurementsSimulation and optimization approaches for humanoid robotsBiologically inspired control algorithms for bipedal walkingGeneration and deformation of natural walking in computer graphicsImitation of human motions on humanoidsEmotional body language during walking Simulation of biologically inspired actuators for bipedal walking machinesModeling and simulation techniques for the development of prosthesesFunctional electrical stimulation of walking
Includes author index
Keywords: Aufsatzsammlung; Humanoider Roboter; Schreitroboter; Bewegungsanalyse; Computersimulation; Gehen; Bipedie